2020
DOI: 10.1111/acer.14422
|View full text |Cite
|
Sign up to set email alerts
|

Association of Alcohol Consumption and Ideal Cardiovascular Health Among South Asians: The Mediators of Atherosclerosis in South Asians Living in America (MASALA) Study

Abstract: Background Observational studies have shown that alcohol consumption above the recommended limit is associated with increased cardiovascular disease (CVD), although its association in South Asians is unclear. Less is known regarding the association between alcohol consumption and cardiovascular health (CVH), assessed by the American Heart Association's Life's Simple 7 (LS7) health metrics among those with South Asian ancestry. Methods This analysis included 701 participants without CVD from the Mediators of At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Study by Chevli et al [145] as a cross-sectional observation with standardized questionnaire administered in interview, which measures alcohol intake on mutually exclusive intervals of never, 1–3, 4–7 and > 7 drinks/week, including 706 South Asian male participants, demonstrated compared to never drinkers those with > 7 drinks/week had lower odds of having intermediate (OR:0.31, 95% CI: 0,10–0.93) and ideal (OR:0.14, 95% CI:0.03–0.60) cardiovascular health on Life‘s Simple 7 (LS-7) metrics yet this association interacted with age and those with < 58 years of age CVH remained similar with alcohol intake, nevertheless those with binge drinking (≥5 drinks in a single day within last month) compared to never drinkers had significantly lower odds for ideal CVH (OR:0.03, 95% CI: 0.003–0.36) regardless of age group.…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 99%
“…Study by Chevli et al [145] as a cross-sectional observation with standardized questionnaire administered in interview, which measures alcohol intake on mutually exclusive intervals of never, 1–3, 4–7 and > 7 drinks/week, including 706 South Asian male participants, demonstrated compared to never drinkers those with > 7 drinks/week had lower odds of having intermediate (OR:0.31, 95% CI: 0,10–0.93) and ideal (OR:0.14, 95% CI:0.03–0.60) cardiovascular health on Life‘s Simple 7 (LS-7) metrics yet this association interacted with age and those with < 58 years of age CVH remained similar with alcohol intake, nevertheless those with binge drinking (≥5 drinks in a single day within last month) compared to never drinkers had significantly lower odds for ideal CVH (OR:0.03, 95% CI: 0.003–0.36) regardless of age group.…”
Section: Cac-development With Progressing Risk Factorsmentioning
confidence: 99%
“…Previous studies have shown that heavy drinking is associated with poorer CVH (Chevli et al, 2020;Ogunmoroti et al, 2019). However, the literature is sparse on the association between alcohol type and CVH, as measured by the AHA's seven CVH metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Although, some of these studies report that light to moderate consumption of wine may be cardioprotective because of the higher concentration of polyphenols (Arranz et al, 2012;Chiva-Blanch et al, 2013;Estruch, 2000), other studies report that this finding may be explained by confounders such as dietary intake, drinking patterns and lifestyle characteristics (Djousse et al, 2009;Gronbaek, 2003;Haseeb et al, 2017;Rimm et al, 1996;Tjonneland et al, 1999). Furthermore, a few epidemiological studies have shown light to moderate alcohol consumption is associated with favorable cardiovascular health (CVH) (Chevli et al, 2020;Ogunmoroti et al, 2019;Piano et al, 2018), defined by the American Heart Association (AHA) as meeting specific criteria for seven CVH metrics (smoking, physical activity, body mass index (BMI), diet, total cholesterol, blood pressure and blood glucose) (Labarthe, 2012;Lloyd-Jones et al, 2010). The CVH metrics are useful surveillance tools to monitor and evaluate the trends of CVD and CVH in the continued efforts to promote and improve global CVH and wellness (Angell et al, 2020;Roger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even more recent observational studies have focused on specific niches of the relationship between alcohol consumption and CVD, testing the hypothesis that the relationship between alcohol and CVD does not fit into a one-size-fitsall approach and that the conflicting results found in previous studies might be due to differences within subpopulations. For example, investigators have observed apparent differences in the alcohol-CVD relationship between African-Americans, Asian-Americans and other race/ethnicity groups found [28][29][30][31][32] (perhaps related to well-known genetic differences in alcohol metabolism [33,34]). Other recent papers have addressed drinking patterns, suggesting that regular drinking and drinking with meals may be associated with a lower risk of mortality [35][36][37] and beverage types, arguing for unique anti-oxidative and antiinflammatory effects of red wine consumption [38].…”
Section: Evidence From Observational Researchmentioning
confidence: 99%